Desain Media Pembelajaran Hidroponik Berbasis Aplikasi Canva dengan Pendekatan Demonstrasi dan Discovery Learning di Era Digital - Muhammad Jailudin (Community : Jurnal Pengabdian Pada Masyarakat, 2026)
This community service was carried out in response to the low utilization of contextual and interactive digital learning media in hydroponic learning at schools. This topic was chosen because hydroponics is highly relevant to environmental issues and food security, and requires a visual, practical learning approach to ensure easy understanding by students. The service activity aims to develop and implement hydroponic learning media using the Canva application, employing a demonstration-and-discovery learning approach. The implementation is carried out in a participatory, applied manner, involving teachers and students as the main subjects of the activity through experiential learning, direct practice, and reflection on the activity's results. The results of the service show an increase in understanding of hydroponic materials, learning activity, and students' positive attitudes toward digital-based learning, accompanied by more collaborative social interaction in the learning process. In addition, students acquired basic hydroponic skills that can be further developed into educational and productive activities. These results confirm that simple, easy-to-use digital learning media can improve learning quality and support the sustainability of community service activities.